1988
DOI: 10.1007/bf02536218
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of cholesterol 5,6‐epoxides with simulated gastric juice

Abstract: Cholesterol 5 alpha,6 alpha-epoxide (alpha-epoxide) and cholesterol 5 beta,6 beta-epoxide (beta-epoxide) were individually suspended in simulated gastric juice (pH 1.2) at 37 C, and their reaction was followed by gradient high performance liquid chromatography (HPLC) with flame ionization (FID) detection. Both epoxides reacted rapidly in the aqueous acid medium. The alpha-epoxide formed 6 beta-chlorocholestane-3 beta,5 alpha-diol (alpha-chlorohydrin) and 5 alpha-cholestane-3 beta,5,6 beta-triol (triol), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…3 gas chromatograph coupled to an SPB-1 fused silica capillary column (60 m×0. 25 Helium was used as the carrier gas, the total run time being 42.5 min. The gas chromatograph was operated in the constant ‰ow mode, with the ‰ow rate set to 1.5 ml He W min.…”
Section: Animals and Permanent Lymph Duct Cannulationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 gas chromatograph coupled to an SPB-1 fused silica capillary column (60 m×0. 25 Helium was used as the carrier gas, the total run time being 42.5 min. The gas chromatograph was operated in the constant ‰ow mode, with the ‰ow rate set to 1.5 ml He W min.…”
Section: Animals and Permanent Lymph Duct Cannulationmentioning
confidence: 99%
“…Therefore, a-and b-epoxycholesterol and cholestanetriol found in the basal lymph might have been derived from the diet. Cholestanetriol might have been derived from a-and b-epoxycholesterols, since Maerker et al 25) have shown that cholestanetriol was easily formed when epoxycholesterols were incubated with gastric juice. Alternatively, we cannot neglect the possibility that the oxysterols found in the basal lymph might have been produced during the preparation.…”
mentioning
confidence: 99%
“…Hydrolysis of epoxy compounds to render the corresponding diols may also occur before absorption, under the acidic conditions in gastric media (Maerker, 1988;Piazza et al 2003;Giuffrida et al 2004). This is of great importance because monoepoxy compounds have been recently found to be one of the major oxidized groups formed at frying temperatures (Velasco et al 2004a(Velasco et al , 2004b, accounting for about 25% of total oxidized fatty acyl groups in real used frying oils at the limit of rejection.…”
Section: Dietary Oxidized Lipids Under Gastric Conditionsmentioning
confidence: 99%
“…Although present in the diet, the epoxycholesterols were not detected at a significant level in the plasma. It is well known that the epoxy-derivatives can be transformed in cholestanetriol in acidic fluid such as stomach secretion (Maerker et al 1988;Schroepfer, 2000). This synthesis can also be carried out by an hepatic epoxide hydrolase (Watabe et al 1980;Sevanian & McLeod, 1986).…”
Section: Sterols In Food Plasma and Heartmentioning
confidence: 99%